Politics and Popular Culture: How Some Young Anglophone Canadians Perceive thePolitical Content of the Entertainment Media - Jackson, David; Darrow, Thomas (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2009)
AbstractThis research, based on surveys of 456 young Canadians enrolled at universitieswhere English is the primary language of instruction, seeks answers to several basicquestions at the foundation of the inquiry into the impact of popular culture onyoung English-speaking Canadians' political beliefs. It investigates whether youngCanadians actually perceive any political messages in popular culture, and whetherthey think about these themes in a rigorous way. We investigate whether conservativeor liberal youths are more likely to agree or disagree with the politics of popularculture, and to what extent young Canadians' attitudes toward the socio-politicalcontent of the entertainment media are different from US youths' attitudes. Thisresearch also serves to link the passive and active theories of socialization, andto contribute to the debate over the existence of US cultural imperialism.